Evaluasi Modul Pelatihan S.E.E.D: Meningkatkan Kompetensi Manajemen untuk Dietisien Menggunakan Kerangka Kerja ADDIE: Perception-Based Evaluation of the S.E.E.D Training Module on Management Skills Development for Dietitians Using the ADDIE Framework - Rusali, Roszanadia; Yusop, Nor Baizura Md; Ghazali, Hazrina; Omar, Noraida; Jamaluddin, Rosita (Universitas Airlangga, 2026)
Background: As the role of dietitians in clinical and operational settings continues to expand, administrative and management skills have become increasingly important. Therefore, the Skills Enhancement for the Excellent Dietitians (S.E.E.D) training module was developed to strengthen dietitians’ management competencies. Objectives: This study was conducted to evaluate the newly developed Skills Enhancement for the Excellent Dietitians (S.E.E.D) training module through participants’ perception-based assessment of management skills development, guided by the ADDIE framework. Methods: A descriptive cross-sectional study was conducted in April 2021 to evaluate S.E.E.D training module using a structured questionnaire. Fifteen government dietitians (U41 and U44) with at least two years of work experience were purposively selected. The module was evaluated using a government assessment form covering five aspects: (i) content, (ii) implementation, (iii) technical and methodology, (iv) benefits, and (v) facilitator effectiveness. Results: Participants reported high satisfaction across all aspects, with mean scores for training content ranging from 4.9 to 5.0. Implementation scores varied between 4.7 and 4.9, with Session 3 (Managing Challenging Behavior) receiving the highest rating (4.9 ± 0.27), while Session 4 (Motivation) had the lowest (4.5 ± 0.33). Most participants indicated being “Very satisfied” or “Satisfied” with the training techniques used. Conclusions: The S.E.E.D training module was well received by participants and demonstrated a high level of satisfaction, aligning with the evaluation objectives. These results provide a strong foundation for further improvement of the module before wider implementation.